Pengaruh Good Corporate Governance Terhadap Profitabilitas Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Syahputri, Lia; Saragih, Fitriani (Politeknik Ganesha Medan, 2024)
This research was conducted with the aim to determine the effect of board of commissioners ownership, board of directors ownership and audit committee ownership on profitability in banking companies listed on the Indonesia Stock Exchange. The population in this study were all banking companies listed on the Indonesia Stock Exchange while the samples that met the observation sampling criteria were conducted for six years and as many as eight banking companies were listed on the Indonesia Stock Exchange. This research approach uses associative research. Data collection techniques in this study using documentation techniques. and the analysis technique used is multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results partial test proves that the board of commissioners ownership and directors ownership variable have a significant effect on profitability while partially it proves that the board of audit committee ownership variables has no effect on profitability in banking companies listed on the Indonesia Stock Exchange